Adopting the FINGER multimodal intervention methodology to prevent cognitive decline in Southern Europe: The GOIZ ZAINDU pilot study. (31st December 2021) - Tainta, Mikel; Ecay, Mirian; Iriondo, Ane; Estanga, Ainara; Clerigue, Montserrat; Saldias, Jon; de Arriba, Maria; Garcia‐Sebastian, Maite; Aurtenetxe, Sara; Barandiaran, Myriam; Gabilondo, Alazne; Mar, Javier; et al.
Abstract: Background: GOIZ ZAINDU ("caring early" in Basque) is a pilot study to adapt FINGER methodology to the Basque Population and evaluate feasibility and adherence to a FINGER‐like multimodal intervention program. Additional exploratory aims included assessment of efficacy on cognition and collection of necessary data to design a large efficacy trial. Method: GOIZ ZAINDU is a one year, randomized, controlled trial of a multimodal intervention in persons aged 60+ with increased CAIDE score (≥ 6), no dementia, and below‐than‐expected performance in at least one of three cognitive screening tests. Participants were recruited from a previous program on early diagnosis and risk awareness (GOIZ‐ALZHEIMER). Randomization to a Multimodal intervention (MI) or to Regular Health Advice (RHA) was stratified by cognitive status (MCI/normal) and age (>/≤ 75). MI included cardiovascular risk factors control, nutritional counseling, physical activity and cognitive training. Primary outcome was adherence to intervention program. Cognitive outcomes included Neuropsychological Test Battery z scores change. Analyses were carried out by intention to treat. Result: 125 participants were recruited (mean age: 75.64 (6.46); 58% women). MI (n=61) and RHA (n=64) groups were balanced in demographics and cognition (Table 1). 52 (85%) participants from RHA and 56 (88%) from MI group completed the study. 55% of participants had attended all intervention activities; 70% attended more than half of cognitive sessions; and 55% attended more than half of cardiovascular, nutritional and physical activity program sessions Risk of cognitive decline was higher in RHA group compared with MI in executive Function (EF)(p=.019) and Processing Speed (PS) scores (p=.026) (Table 2). 32 (64%) participants In the RHA and 22 (40%) in the MI group declined in EF; 30 persons (61%) in the RHA and 22 (39%) in the MI declined in PS, Conclusion: The GOIZ‐ZAINDU study has proved that the FINGER methodology is adaptable and feasible in a different socio‐cultural environment. Exploratory efficacy results show lower risk of decline in EF and PS. These results support the design of a large‐scale efficacy FINGER‐like trial in Southern Europe, the GO‐ON study.